1998
DOI: 10.1002/mrm.1910400318
|View full text |Cite
|
Sign up to set email alerts
|

In vivo perfusion measurements in the human placenta using echo planar imaging at 0.5 T

Abstract: This paper presents the first in vivo measurements of perfusion in the human placenta from 20 weeks gestational age until term, using the non-selective/selective inversion recovery echo-planar imaging sequence, in which data is alternately acquired following a selective and non-selective inversion pulse. Twenty pairs of images were collected, two each at the following inversion times: 20, 310, 610, 910, 1110, 1410, 1910, 2810, 3310, and 4510 ms with the sequence being repeated with a repetition time (TR) of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 13 publications
8
49
0
Order By: Relevance
“…To date, only two studies have explored the use of in vivo FAIR imaging in the placenta, likely due to the difficulty in reliably acquiring perfusion data in the placenta. Although FAIR imaging did not reveal differences in perfusion between healthy and compromised pregnancies in one study (80), when the authors generated perfusion maps, they reported decreased perfusion fraction in pregnancies complicated by FGR. The authors speculate that perfusion maps were more representative of overall blood movement, given the multi-directional flow and could be used to distinguish normal and pathologic pregnancies (80).…”
Section: Role Of Magnetic Resonance Imaging In Assessing Placental Hementioning
confidence: 94%
“…To date, only two studies have explored the use of in vivo FAIR imaging in the placenta, likely due to the difficulty in reliably acquiring perfusion data in the placenta. Although FAIR imaging did not reveal differences in perfusion between healthy and compromised pregnancies in one study (80), when the authors generated perfusion maps, they reported decreased perfusion fraction in pregnancies complicated by FGR. The authors speculate that perfusion maps were more representative of overall blood movement, given the multi-directional flow and could be used to distinguish normal and pathologic pregnancies (80).…”
Section: Role Of Magnetic Resonance Imaging In Assessing Placental Hementioning
confidence: 94%
“…70 Human studies ASL MRI was first developed to study perfusion in the brain, kidney, retina, and some tumors. 68 36,38 The perfusion map showed more areas of low perfusion in relation to a decrease in placental perfusion in IUGR pregnancies (923 vs 2359 arbitrary units; P ¼ .003) 38 ; a correlation with the uterine artery pulsatility index was established later (Table 2). 77 Limitations Although ASL MRI can yield a quantitative estimate of placental perfusion without using an exogenous contrast agent, only a few studies have been published since the seminal publications in 1998.…”
Section: Ajogorgmentioning
confidence: 97%
“…77 Limitations Although ASL MRI can yield a quantitative estimate of placental perfusion without using an exogenous contrast agent, only a few studies have been published since the seminal publications in 1998. 36,38 The limitations of this technique are a poor signal-to-noise ratio (SNR) with most methods, owing to small measurable differences between tagged and untagged images and an important sensitivity to motion, transit delay, and resonance offset artifacts. 67 Future challenges ASL remains the only fMRI technique that allows the measurement of tissue perfusion with no exogenous contrast agent.…”
Section: Ajogorgmentioning
confidence: 99%
“…[9][10][11][12][13] Perfusion can be measured in several ways with MRI, including arterial spin labelling (ASL), echo planar imaging (EPI), and intravoxel incoherent motion (IVIM). [14][15][16] We have previously described a novel MRI-based approach to study placental function in a living mouse model, based on the use of gadolinium contrast agents and dynamic contrast enhancement (DCE) MRI. This has the capacity to measure placental perfusion and permeability in both physiological and pathological settings; 10,[12][13][14][15][16] however, gadolinium is not recommended for use during human pregnancy.…”
Section: Introductionmentioning
confidence: 99%